(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Oil and gas are major energy sources that continue to maintain their strategic importance in meeting the needs of life and industry, despite the availability of other energy alternatives. With growing global demand and declining proven reserves, there is a need to enhance the production efficiency of discovered fields. Among the newly adopted methods for increasing production and improving operational performance is the use of stratified water injection, which aims to maintain stratified pressure and reduce the environmental impacts resulting from associated water. However, this method faces operational challenges, most notably the accumulation of sediments within injection systems, leading to a decrease in operational efficiency. Techniques for treating these sediments vary between mechanical, chemical, and magnetic. This study focused on the use of magnetic technology due to its high efficiency, low operating costs, and flexibility compared to other methods. A laboratory study was conducted using a water model taken from an Iraqi field to evaluate the effect of fluid velocity on electrical conductivity, an indirect indicator of sediment removal effectiveness. The results demonstrated the ability of magnetic treatment to effectively reduce sedimentation under specific operating conditions, enhancing its potential for application in field settings as an economical and practical solution.